Upaya Guru PAI dalam Mengevaluasi Hasil Belajar Pendidikan Agama Islam Siswa di SMPN 3 Ponjong - Janah, Hanifah Miftahul; Inayati, Nurul Latifatul (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study examines the efforts of Islamic Religious Education (PAI) teachers in evaluating student learning outcomes at SMPN 3 Ponjong, Gunungkidul, Yogyakarta. The background of this study is the decline in students' enthusiasm and focus in learning PAI in class. The purpose of this study is to identify the forms of evaluation used by PAI teachers. Using descriptive qualitative research methods with a case study approach, researchers collected data through observation, interviews, and documentation. Triangulation of methods and sources was used to test the validity of the data, while data analysis used the Miles and Huberman technique which includes data reduction, data presentation, and conclusion drawing. The results showed that PAI teachers implemented three types of learning evaluation. First, formative assessment through daily assignments in the form of practice questions that allow teachers to monitor the development of students' understanding in real-time and provide immediate feedback. Second, summative assessment carried out at the end of the learning period using test (oral and written) and non-test (performance, work, and portfolio) techniques. Report card scores show good cognitive achievement, although weaknesses are still found in aspects of religious practice such as reading and writing the Qur'an. Third, authentic assessment assesses students' ability to apply knowledge to real contexts through projects to make learning videos of worship and direct practice of religious activities. These three evaluation methods proved effective in improving students' conceptual understanding and practical skills, as well as increasing motivation and learning focus. This study concludes that a comprehensive evaluation approach that covers cognitive, affective, and psychomotor aspects is essential in PAI learning to ensure students not only understand the theory of Islamic teachings but are also able to apply it in their daily lives.